Expression of matrix metalloproteinase-2 and 9 with their inhibitors, tissue inhibitors of metalloproteinase-1 and 2 in oral lichen planus - Natheer Hashim Al-Rawi; Thaer Kassim Al-Kassam; Ahlam Hameed Majeed (Wolters Kluwer Medknow Publications, 2014)
Objectives: The study aims to explore the expression of the matrix metalloproteinases (MMP-2, -9) and their inhibitors (tissue inhibitors of metalloproteinase [TIMP]-1, -2) as well as the correlation between them in the different morphological forms of oral lichen planus (OLP). Materials and Methods: 28, formalin-fixed, paraffin-embedded specimens of OLP and six specimens of squamous cell carcinoma, which served as the positive control and another six normal oral tissue specimens, which served as the negative control were used in this study. All the 40 samples were investigated immunohistochemically for the expression of MMP-2, -9 with their tissue inhibitors TIMP-1, -2. Results: The immune reactivity of MMP-2, -9, TIMP-1 and TIMP-2 were detected at significant levels within the keratinocytes and lymphocytes of the OLP cases when compared with the normal control group (P < 0.0001) while the MMP-2, -9 immune reactivity was found to be about 1/5-1/10 of that detected in the positive control group. The TIMP-1, -2 were strongly expressed in both keratinocytes and lesional lymphocytes. However, no significant relationship was discovered between the expressions of MMP-2, MMP-9, TIMP-1 and TIMP-2 and the morphological types of OLP. Conclusion: A distinct imbalance is observed between the MMP and TIMP activities when the normal mucosa and OLP sample are compared. The TIMP intensities, on the other hand, were found to be very high, suggesting an endogenous protection of the basement membrane against the degrading effect of the MMP enzymes.